Natural vitamin D3 response elements formed by inverted palindromes: polarity-directed ligand sensitivity of vitamin D3 receptor-retinoid X receptor heterodimer-mediated transactivation. - Schräder, M (1995)
VDR, the nuclear receptor for 1,25-dihydroxyvitamin D3 (VD), is a member of the superfamily of nuclear hormone receptors and controls multiple aspects of homeostasis, cell growth, and differentiation. VDR can function as a homodimer, but heterodimerization with the retinoid X receptor (RXR), retinoic acid receptor, or thyroid hormone receptor increases its affinity for response elements in the promoter of target genes. All natural VD response elements identified so far consist of direct repeats of a variety of hexameric core binding motifs with a preferential spacing of three nucleotides (DR3s). However, all four VD signalling pathways function also on response elements formed by inverted palindromes, although these sequences were not of natural origin. Here, we report the identification of two VD response elements consisting of inverted palindromes spaced by nine nucleotides (IP9s) in the promoters of the human calbindin D9k gene and the rat osteocalcin gene. Like most DR3-type VD response elements, both IP9s are preferentially bound by VDR-RXR heterodimers with a 5'-RXR-VDR-3' polarity, whose transcriptional activity can be enhanced by costimulation with 9-cis retinoic acid. We demonstrate that changing the response element orientation relatively to the basal promoter decreases the sensitivity of transcriptional activation by VD by about 10-fold. Our findings indicate that inverted palindromes are as functional as direct repeats. Furthermore, we suggest that the orientation of a nuclear receptor complex in relation to the basic transcriptional machinery, which is directed by heterodimer polarity and response element orientation, influences the ligand sensitivity of the respective target gene expression.